Structural comparison of human and Plasmodium proteasome β5 subunits: informing selective inhibitor design for anti-malaria agents - Muhammad Yasir; Jinyoung Park; Eun-Taek Han; Won Sun Park; Jin-Hee Han; Wanjoo Chun (Malaria Journal)
Abstract Background The Plasmodium proteasome emerges as a promising target for anti-malarial drug development due to its potential activity against multiple life cycle stages. Methods In this investigation, a comparative analysis was conducted on the structural features of the β5 subunit in the 20S proteasomes of both Plasmodium and humans. Results The findings underscore the structural diversity inherent in both proteasomes. The human proteasome β5 subunit reveals a composition rich in β-sheets and adopts a more compact conformation. This structural arrangement limits the ligand binding pocket's capacity to accommodate only small compounds effectively. In contrast, the Plasmodium β5 subunit exhibits a higher prevalence of loop structures, creating a more open and flexible binding pocket. This unique structural characteristic enables the binding of a larger and more diverse array of compounds. Conclusion The discernible structural contrast between the human and Plasmodium proteasome β5 subunits holds promise for the identification of Plasmodium-selective compounds. The ability of the Plasmodium proteasome to accommodate a broader range of compounds due to its distinctive structural features opens avenues for drug screening to intending to develop selective anti-malarial agents. This study contributes valuable insights into the structural basis for targeting the Plasmodium proteasome and paves the way for the rational design of compounds with enhanced specificity and efficacy against malaria.